LITERATURE REVIEW ON THE USE OF E-LEARNING FOR ISLAMIC RELIGIOUS EDUCATION LEARNING - Adinda, Charisma; Koderi; Agus Jatmiko; Ihsan Mustofa (CV. Fahr Publishing, 2024)
This research aims to explore the effectiveness of using e-learning in learning Islamic Religious Education along with its benefits, challenges, and impacts. The method used in this research uses the literature review method by using data in the form of published articles obtained through Google Scholar and Publish or Perish. The results of this study show that the use of e-learning in learning Islamic Religion has good effectiveness or impact. E-learning is able to provide a variety of advantages and benefits that greatly benefit teachers and students, but there are also shortcomings that should continue to be evaluated. The development of e-learning is very important to be done by teachers so that students continue to be motivated in learning, so that the messages and values in Islamic teachings can be conveyed to students. This research provides an important contribution to Islamic learning in the form of alternative methods in integrating technology, accessibility, monitoring, evaluation, improving the quality of learning, and increasing student involvement using e-learning in Islamic learning